Ethnobotanical Survey of Plants Used in The Management of Peptic Ulcer Diseases in Wukari Metropolis - Akpevwoghene Agbatutu; Efosa A. Ogie-Odia; Mary Oromioshemime Ifedele; Funmilola Modinat Abdulrasaq; Daniel Eseigbe; Francis Nosakhare Imade (Biology, Medicine, & Natural Product Chemistry, 2022)
Peptic ulcer diseases (PUD) are sores formed in soft tissues present in the lining of the digestive tract as a result of excessive stomach acid or inability of the alimentary tract or stomach to protect itself. The increasing surge for plant based drugs in the management of PUD has increased scientific investigation of herbs and recipes from traditional medicinal practitioners (TMP) to ascertain their efficacy through pharmacological studies. Ethnobotanical survey of plants and recipes from TMP used in the management of PUD in Wukari metropolis, Taraba State, Northeastern Nigeria were documented. A total of twenty (20) TMP located in ten (10) different area of the town were interviewed using a semi structured questioner. Twenty-four (24) plant species from twenty (20) different families and sixteen (16) recipes were documented from the survey. It was observed that plant leaves were mostly used while C. longa (Zingberaceae), M. paradisiaca (Musaceae) had the highest frequency of occurrence in recipes formulation. Therefore, due to the proven efficacy of these herbal recipes as reported from correspondents, there is need for proper documentation, conservation, cultivation and use of these medicinal plants in the management of PUD to avoid them being endangered or going into extinction.